Penerapan Metode Content and Language Integrated Learning (CLIL) dalam Pembelajaran untuk Mengatasi Hambatan Bahasa Indonesia di Saengsattha School, Thailand - M.Rafi; Al-Khowarizmi (Tarbiyah bil Qalam : Jurnal Pendidikan Agama dan Sains, 2026)
This study investigates the application of Content and Language Integrated Learning (CLIL) to overcome Indonesian language barriers at Saengsattha School in Southern Thailand, where multilingual students encounter academic vocabulary limitations and speaking anxiety. The objective is to evaluate CLIL's effectiveness in enhancing elementary students' language proficiency. Employing a quasi-experimental one-group pre-test post-test design, the population comprised Prathom 4-6 students, with a purposive sample of 45 (Prathom 4: 13, Prathom 5: 15, Prathom 6: 17). Written tests assessed basic vocabulary, pronouns, and simple sentences, analyzed through descriptive statistics (means, differences, percentages). Results indicate scores improved from 56.2 (pre-test) to 75.8 (post-test), a 34.9% increase. The conclusion affirms CLIL effectively supports contextual language mastery and reduces affective barriers in multilingual settings.